The Politics of Progressivity: Court-Ordered Reforms, Racial Difference, and School Finance Fairness. (December 2022) - Oberfield, Zachary W.; Baker, Bruce D.
This article contributes to our understanding of American education politics by exploring when and why states redistribute K–12 education dollars to poorer schools. It does so by examining three explanations for intrastate changes in progressivity: court-ordered finance reforms, political trends, and demographic changes. Using state-level data from 1995 to 2016, we find mixed evidence that progressivity increased following a court-ordered school-finance overhaul. Rather, we show that changes in progressivity were most consistently tied to changes in student demography: As students became poorer, or more racially diverse, lawmakers created less progressive finance systems. The article concludes by discussing what these findings mean for advocates seeking to protect and advance gains in education-spending progressivity.